Promoting Self-regulated Learning of Brazilian Preservice Student Teachers: Results of an Intervention Program - Ganda, Danielle Ribeiro; Boruchovitch, Evely (Frontiers in Education, 2018)
Self-regulation is the process by which individuals monitor, control, and reflect on their learning. Self-regulated students have motivational, metacognitive, affective, and behavioral characteristics that enhance their learning. As the importance of self-regulated learning is well acknowledged by research nowadays, the aim of this study is to examine the effectiveness of an innovative course designed to promote self-regulated learning among Brazilian preservice student teachers. The innovative approach was developed in the format of a program of intervention based heavily on self-reflection. The content involved student exposure to self-reflexive activities, lectures on the self-regulated learning framework, and theoretical tasks aimed at fostering self-regulation of students in a double perspective: as a student and as a future teacher. The efficacy of the approach was tested by comparison with both the results of students who had taken a course with theoretical content only and those who had not taken any course at all. The sample consisted of 109 students in 4 different freshman classes in a Teacher Education Program in a Brazilian public university in an inner city in the state of São Paulo. The research was conducted using a quasi-experimental design with three stages: pretest, intervention, and posttest. The classes were randomly assigned to experimental and control conditions as follows: an experimental group involving intervention, an experimental group exposed to theory, and two control groups not taking the course. Before and after the intervention program, all the participants responded to the Learning and Study Strategies Inventory and the Self-efficacy for Self-regulated Learning scales. Overall, the results showed that the intervention program format had a positive impact in enhancing student self-regulation. Moreover, students in both the experimental groups reported both higher gains in self-efficacy for self-regulated learning scores and an increase in employment of learning strategies when compared to the control groups.